Analisis Kekuatan Pencahayaan Lampu Dalam Sistem Penerangan Jalan Umum Tenaga Surya 200wp - kusumo, bayu (Universitas Pancasakti, 2024)
Lighting is a vital requirement for elements of human activity, especially during productive hours of human activity. The important role of electricity in supporting the progress of lighting process technology, mechanical and other automation cannot be missed. Light is an electromagnetic wave consisting of a magnetic field and an electric field that are perpendicular to each other and light can also experience reflection, diffraction, refraction, polarization and interference. Light in its design is a lumen with flux units emitted in solid angle units by a source with a light intensity of one Candela. Lux is a metric unit of measurement for light on a surface. Efficacy is the average illumination / brightness achieved in a flat work area per watt in general lighting in the room expressed in lux/Watt/m2. Field studies, namely by observing and collecting data directly in the field for research objects on 40 watt LED lights installed in Solar Public Street Lighting on the Krisnadwipayana University Campus, as a reference for the design and installation and location of Solar Public Street Lighting placement. Testing the lighting data collection point (lux) is carried out to determine the angle of emitted lighting (lux) and the level of lighting radius obtained based on field data. As a result to find out according to standardization (SNI 7391; 2008). The street lighting for theenormous Solar Street in the parking lot of the Krisnadwipayana University Laboratory uses LED lamps with a flux of 5778 lumens and a power of 40 watts. The average lumen from the results of observations of data collection corresponds to the height distance between the LED 6 meters and the lux meter, and the angle of 5o is 53 lux. Keyword : Light, Lumen, Lux and Efficacy, Electrical Energy.